Knowledge, attitude, and practice of COVID-19 among individuals belonging to rural part of Bihar: A cross-sectional study - Rituraj Kotoki; Saurabh Bobdey; Nikunj Kumar Kansara; Arun Kumar Yadav (Wolters Kluwer Medknow Publications, 2023)
Aim and Objective: This study aimed to assess the knowledge, attitude, and practices of individuals residing in the rural part of Bihar toward COVID-19. Methods: We conducted a cross-sectional study from September 10, 2020, to September 29, 2020, with the help of a prevalidated questionnaire. The questionnaire was distributed to individuals living in the different rural parts of the Patna district in Bihar. People from the age group of 16 years and above were included in the study. Health-care workers, Anganwadi workers, and Accredited Social Health Activists (ASHA) were excluded from the study. Results: Out of 385 study participants, 58.7% were males. The majority of the respondents belonged to the age group of 26-35 years (39.2%). 64.9% of the study participants were working in the private sector, and 5.5% were unemployed. The majority of the participants (98.44%) agreed regarding the seriousness of the COVID-19 pandemic and had adequate knowledge about symptoms of COVID-19. The female knowledge score was slightly more than males, but the difference was not statistically significant (P > 0.5). Furthermore, 97.4% of the study participants were aware that there is no specific cure for the disease. Higher income was associated with higher knowledge, attitude, and practice. Conclusion: The participants had significant knowledge about COVID-19 and acceptable practices toward its protective measures. However, there was continuing movement of participants to meet relatives and friends.